Isolation and Characterization of a Thermotolerant Acetic Acid Bacteria Strain for Improved Zhenjiang Aromatic Vinegar Production - Yuqin Wang; Shengkai Hua; Leyi Wang; Chunjia Bao; Xinnuo Chen; Xiang Wei; Yongjian Yu (Foods)
This study aimed to isolate a thermotolerant acetic acid bacteria (AAB) strain from Zhenjiang aromatic vinegar (ZAV) and evaluate its potential as a starter culture for high-temperature solid-state vinegar fermentation. Acetobacter pasteurianus TCBRC 103 was successfully isolated and demonstrated superior thermotolerance compared to the industrial strain A. pasteurianus Huniang 1.01. A. pasteurianus TCBRC 103 exhibited robust growth and acetic acid production at 42 °C. When employed in the solid-state fermentation of ZAV, inoculation with A. pasteurianus TCBRC 103 resulted in higher fermentation temperatures, leading to enhanced accumulation of organic acids and volatile compounds. Notably, the concentrations of flavor compounds such as isoamyl acetate, acetic acid 2-phenylethyl ester, and acetoin were significantly higher in vinegar fermented by A. pasteurianus TCBRC 103 compared to those fermented by A. pasteurianus Huniang 1.01. Orthogonal partial least squares-discriminant analysis (OPLS-DA) identified 14 discriminative flavor compounds that could serve as potential markers for distinguishing between vinegars fermented by A. pasteurianus TCBRC 103 and A. pasteurianus Huniang 1.01. These findings highlight the promising application of A. pasteurianus TCBRC 103 as a starter culture for the production of high-quality ZAV under high-temperature conditions, with implications for reducing cooling costs and improving vinegar productivity in industry.